2015
DOI: 10.1016/j.tecto.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Geology of the Eoarchean, > 3.95 Ga, Nulliak supracrustal rocks in the Saglek Block, northern Labrador, Canada: The oldest geological evidence for plate tectonics

Abstract: The Earth is a unique planet, which has been highly evolved, diversified and complicated through geologic time, and underwent many key events, including giant impact, magma ocean, core formation, large-scale mantle differentiation and late heavy bombardment, especially in its dawn. But, our knowledge of early Earth is limited due to the lack of the Hadean supracrustal rocks. The supracrustal rocks with the Eoarchean ages provide key evidence for the Earth's early evolution, but few supracrustal rocks have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(50 citation statements)
references
References 174 publications
(270 reference statements)
0
49
0
1
Order By: Relevance
“…The dominant component of the Saglek Block is the Uivak gneiss, which is subdivided into two types: Eoarchean (> 3.6 Ga) Uivak I gneisses of tonalite-trondhjemite-granodiorite (TTG) composition, and slightly younger (~3.6 Ga) Uivak II augen gneisses, which include Fe-rich porphyritic granodiorites and diorites (Bridgwater and Schiøtte, 1991;Collerson and Bridgwater, 1979). The Uivak I gneiss is a composite of different magmatic protoliths, and contains enclaves of Fe-rich monzodiorites (Collerson et al, 1992) and tonalities (Komiya et al, 2015). These authors have suggested the enclaves were derived from > 3.9 Ga protoliths, the 'Nanok' and 'Iqaluk' gneisses, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The dominant component of the Saglek Block is the Uivak gneiss, which is subdivided into two types: Eoarchean (> 3.6 Ga) Uivak I gneisses of tonalite-trondhjemite-granodiorite (TTG) composition, and slightly younger (~3.6 Ga) Uivak II augen gneisses, which include Fe-rich porphyritic granodiorites and diorites (Bridgwater and Schiøtte, 1991;Collerson and Bridgwater, 1979). The Uivak I gneiss is a composite of different magmatic protoliths, and contains enclaves of Fe-rich monzodiorites (Collerson et al, 1992) and tonalities (Komiya et al, 2015). These authors have suggested the enclaves were derived from > 3.9 Ga protoliths, the 'Nanok' and 'Iqaluk' gneisses, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Based on Nd-Sm bulk-rock analyses, O'Neil et al (2008O'Neil et al ( , 2011 reported the existence of yet older ϳ4.28 Ga rocks in the Nuvvuagittuq greenstone belt, northeastern Canada, but Cates et al (2013) indicated a possible maximum age of ϳ3.78 Ga for these supercrustals. In any case, water-laid metasedimentary rocks in western Greenland requires that tracts of the Earth's surface had cooled below the boiling point of H 2 O by ϳ3.8 Ga at the very latest (Moorbath et al 1972;Moorbath 1984;Nutman et al 1997;Komiya et al 2002Komiya et al , 2015 but possibly up to at least 300 Myr earlier (Wilde et al 2001;Mojzsis et al 2001, Valley et al 2002Harrison 2009;Sleep et al 2014). Apparently, segments of solid crust and mantle were present in the early Earth (Davies 2006(Davies , 2007Hynes 2008).…”
Section: Formation Of the Earthmentioning
confidence: 99%
“…Bulk-rock isotopic data suggest that thorough reincorporation of sialic materials into the mantle continued until ϳ3.8 Ga, that the average age of continental crust separated from the mantle is ϳ2.3 ± 0.5 Ga, and that much of this material (70% or more) was generated by Late Archean or Early Proterozoic time (Veizer 1976;Jacobsen and Wasserburg 1981;DePaolo 1981;Nelson and DePaolo 1985;Taylor and McLennan 1985;Turcotte and Kellogg 1986;DePaolo et al 1991;Condie 1998;Hawkesworth et al 2013). Calcalkaline igneous arcs also were produced by Hadean subduction, but long-term preservation of continental crust did not begin until the Early Archean (Moorbath et al 1972;Komiya et al 2015). The existence of igneous zircons as old as ϳ4.3-4.2 Ga (Compston and Pidgeon 1986;Wilde et al 2001;Harrison 2009;Hopkins et al 2008Hopkins et al , 2010 in mid-Archean sedimentary rocks reflects at least short-term near-surface retention of some ancient arc material.…”
Section: Separation and Growth Of The Continental Crustmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore Hadean mantle geochemical domains and maybe even Hadean crust exist on the Earth [e.g., O'Neil et al ., ]. For reference, the oldest undisputed sedimentary rocks on the Earth are 3.95 Ga [ Komiya et al ., ].…”
Section: Modeling Approaches With Regard To Veneer Componentmentioning
confidence: 99%